(untitled) (Ibrahim Cardiac Medical Journal, 2017)
Objective: The present quasi-experimental (comparative clinical trial) study was conducted to compare the outcome of active versus conservative management in patients with prelabour rupture of membrane (PROM) at term with an unfavourable cervix. Materials & Methods: The study was carried out at Gynae & Obstetrics Department, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka over a period of 12 months from July 2009 to June 2010. Women admitted in the Obstetrics & Gynaecology Ward of BSMMU with pre-mature rupture of membrane (PROM) at term with unfavourable cervix was the study population. A total of 86 women with rupture of membranes at > 37 weeks of gestation with a single foetus in a cephalic presentation, Bishop’s score below 6, absence of active labour, no history of previous uterine surgery, no contraindication to vaginal delivery, a normal cardiotocogram and an adequate pelvis on clinical pelvimetry were included in the study and divided into two groups – study group (who received 25 μg of misoprostol every 6 hours in the posterior fornix of the vagina to a maximum of 4 doses) and control (who received conservative treatment for 24 hours). Result: The result shows that the study and control groups were almost identical in terms of age (p = 0.058), parity (p = 0.812), H/O past abortion (p = 0.366). Majority (94.3%) of the patients in case group and 64.4% in control group took 24 or < 24 hours to deliver their babies. The mean interval between PROM and uterine contraction and that between ROM and delivery were significantly less in the study group than those in the control group (p < 0.001 and p < 0.001 respectively). About 63% of study group experienced significant uterine contractions after 1st dose, 23.3% after 2nd dose, 9.3% after 3rd dose and 4.7% after 4th dose of misoprostol, while none of the patients in control group experienced significant contraction during the same period (p < 0.001). Twenty two (50.6%) of controls needed oxytocin for induction as opposed to none in the study group. The need for oxytocin during labour in study group were significantly less (37.2%) than that in control (80.5%) (p= 0.024). The incidence of failed induction was even less in study group (11.6%) than that in control (44.2 %) (p = 0.001). Two (4.7%) patients in the study group developed uterine hyperstimulation, 2.3% uterine tachysystole and another 2.3% nausea/vomiting while none of patients in control group developed the same complications. One (2.3%) of the patients in study group experienced chorioamnionitis and 9.3% exhibited group-B streptococci in high vaginal swab culture. In contrast, 18.6% of the controls developed chorioamnionitis and 14% showed the presence of group-B streptococci in high vaginal swab. In terms of mode of delivery, normal vaginal delivery (NVD) occurred in 88.4% study group as compared to 53.5% of control group (p<0.001). There was no significant difference between the groups in terms of foetal distress (p= 0.747) and neonatal sepsis (p = 0.121). Over half of the patients in the both groups had a history of less than 4 vaginal examinations during labour. There was no significant differences between the groups with respect to Apgar score at 1 minute of birth, neonatal sepsis and foetal distress (p=0.063, p=0.121 and p=0.747 respectively). Conclusion: The study concluded that management of premature rupture of membrane with unfavourable cervix using vaginal misoprostol increases the rate of normal delivery thereby reducing the risk of caesarean section, while conservative management of premature rupture of membrane usually fails to augment normal delivery. So it is safer to give induction to women presenting with premature rupture of membrane with unfavourable cervix using vaginal misoprostol. Ibrahim Card Med J 2015; 5 (1&2): 35-39